Thanksgiving thief - Keene, Carolyn (Keene, Carolyn. Nancy Drew and the clue crew, 2008)
As Thanksgiving food around town starts to disappear, the Clue Crew realizes that someone is trying to destroy the holiday! Read along to see if the Clue Crew can catch these birdbrained bandits, or if Thanksgiving dinner turns into a recipe for disaster.